2009
DOI: 10.1186/1476-4598-8-30
|View full text |Cite
|
Sign up to set email alerts
|

Corticotropin Releasing Factor promotes breast cancer cell motility and invasiveness

Abstract: Introduction: Cancer cells secrete bioactive peptides that act in an autocrine or paracrine fashion affecting tumor growth and metastasis. Corticotropin-releasing factor (CRF), a hypothalamic neuropeptide that controls the response to stress, has been detected in breast cancer tissues and cell lines. CRF can affect breast cancer cells in an autocrine or paracrine manner via its production from innervating sympathetic neurons or immune cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
1
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 56 publications
4
33
1
4
Order By: Relevance
“…The other CRF receptor subtypes were not detected. Interestingly, while CRF transiently inhibited apoptosis, it also promoted cell motility and invasiveness most probably via induction of focal adhesion kinase phosphorylation, actin filament reorganization, and production of prostaglandins via Cox 1 [40]. These findings support a role of the CRF system (CRF/CRF1) in breast cancer cell growth, homeostasis, motility, and metastatic potential.…”
Section: Crf and Breast Cancersupporting
confidence: 63%
“…The other CRF receptor subtypes were not detected. Interestingly, while CRF transiently inhibited apoptosis, it also promoted cell motility and invasiveness most probably via induction of focal adhesion kinase phosphorylation, actin filament reorganization, and production of prostaglandins via Cox 1 [40]. These findings support a role of the CRF system (CRF/CRF1) in breast cancer cell growth, homeostasis, motility, and metastatic potential.…”
Section: Crf and Breast Cancersupporting
confidence: 63%
“…Ciocca et al detected high levels of CRH in the biopsies of breast cancer (13). It is also reported that CRH can promote the cell motility and invasiveness in MCF-7 cancer cells (16). The present study has added novel information in this area by showing that CRH is detected in GC tissue as well as in the gastric mucosa with chronic gastritis.…”
Section: Discussionmentioning
confidence: 58%
“…Other researchers also found the relationship between CRF family and cell migration. Ariadne Androulidaki reported that CRF induced prostaglandins production to stimulate cell motility and invasiveness of MCF7 cells [28]. Jo YH pointed out that CRF enhanced Ishikawa cell migration by increasing MMP-2 and MMP-9 [29].…”
Section: Discussionmentioning
confidence: 98%